Staphylococcal superantigen‐like proteins interact with human MAP kinase signaling protein ERK2. Issue 2 (11th September 2019) - Dutta, Debabrata; Mukherjee, Devdeep; Mukherjee, Indranil Arun; Maiti, Tapas Kumar; Basak, Amit; Das, Amit Kumar
Abstract : This study aimed to identify the intracellular binding partner of a unique class of staphylococcal secreted exotoxins called superantigen‐like proteins (SSL) from human macrophage and keratinocyte cell lysates. Here, we report that SSL1 specifically binds to human extracellular signal‐regulated kinase 2 (hERK2), an important stress‐activated kinase in mitogen‐activated protein kinase signaling pathways. Western blot and in vitro binding studies with recombinant hERK2 confirmed the binding interaction of SSL1, SSL7, and SSL10 with hERK2. Moreover, the SSLs‐hERK2 interaction was validated biochemically by ELISA. Our finding shows that SSLs play a novel role by binding with host cell MAP kinase signaling pathway protein. Understanding the SSL‐hERK2 interaction will also provide a basis for designing SSL‐based peptide inhibitors of hERK2 in cancer therapy. Abstract :